2023
DOI: 10.3233/cbm-220041
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating gliomas with FGFR alterations: Histologic features, genetic alterations, and potential clinical implications

Abstract: BACKGROUND: Fibroblast growth factor receptors (FGFRs) are frequently altered in cancers and present a potential therapeutic avenue. However, the type and prevalence of FGFR alterations in infiltrating gliomas (IGs) needs further investigation. OBJECTIVE: To understand the prevalence/type of FGFR alterations in IGs. METHODS: We reviewed clinicopathologic and genomic alterations of FGFR-mutant gliomas in a cohort of 387 patients. Tumors were examined by DNA next-generation sequencing for somatic mutations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…This could stem from the bidirectional effects of TERT mutations, where the neuroprotection and tumor growth effects counteract each other. Furthermore, the fibroblast growth factor receptor (FGFR) gene, frequently altered in cancer, particularly in diffuse gliomas (64.3%) (Dono et al 2023 ), has been found played a potential role in neural architecture in central demyelinating diseases (Zhang et al 2023 ). FGFR proved to help manage neuroinflammation and promote nerve repair and recovery of motor function in multiple sclerosis (MS) patients (Zhang et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could stem from the bidirectional effects of TERT mutations, where the neuroprotection and tumor growth effects counteract each other. Furthermore, the fibroblast growth factor receptor (FGFR) gene, frequently altered in cancer, particularly in diffuse gliomas (64.3%) (Dono et al 2023 ), has been found played a potential role in neural architecture in central demyelinating diseases (Zhang et al 2023 ). FGFR proved to help manage neuroinflammation and promote nerve repair and recovery of motor function in multiple sclerosis (MS) patients (Zhang et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have highlighted differences in methylation profiles, tumor mutational burdens (TMBs), and copy number alterations between F3T3-positive and -negative GBMs [5,12]. Some previous studies have been conducted on F3T3-positive GBMs from multiinstitutional cohorts [8,13], but their clinicopathological features remain to be clarified. In this study, we aimed to comprehensively analyze the clinical manifestations, imaging findings, histological features, and molecular characteristics of 25 consecutive cases of F3T3-positive GBM diagnosed at a single institution.…”
Section: Introductionmentioning
confidence: 99%